Reasoning of business strategic decisions selection - Bivainis, Juozas; Zinkevičiūte, Virgilija (Technological and Economic Development of Economy, 2006)
This article analyzes reasoning of strategic business decisions selection. In order to accomplish the task the synthesis of two methods is offered – scenario and multicriteria evaluation of strategic decisions. The base of multicriteria evaluation of strategic decisions is set onto the tree‐level criteria system (primary, partially integrated and complex‐integrated criteria). Relatives weights of the primary and partially integrated criteria is taken in to account in the calculation of a complex‐integrated criterion impact. Also the methodical usage of guidelines of scenario and multcriteria evaluation method synthesis as well as verification of its results through an experiment are presented in the article. The following advantages are typical for the synthesis of these two methods:• decisions evaluation is accurate, complex and performed accordingly to environmental variety;• the decisions are being evaluated while using a broad criteria system which leaves an opportunity to fully judge the suitability of certain decisions to the business subject;detailed evaluation results support strategic decisions making based on acceptable level the risk, environmental clauses and results of complex evaluation;evaluation becomes understandable, clear and visual to all within the business subject.Article in Lithuanian.Verslo strateginių sprendimų pasirinkimo pagrindimasSantrauka. Straipsnyje nagrinėjama strateginių sprendimų pasirinkimo pagrindimo problema. Tam siūloma taikyti strateginių sprendimų daugiakriterio vertinimo ir scenarijų metodo sintezę. Daugiakriterio vertinimo branduolį sudaro trijų pakopų kriterijų (pirminių, dalinių integruotų, kompleksinio integruoto) sistema. Apskaičiuojant kompleksinio integruoto kriterijaus reikšmę, atsižvelgiama į pirminių ir dalinių integruotų kriterijų santykinį reikšmingumą. Pateiktos strateginių sprendimų pagrindimo, taikant daugiakriterio vertinimo ir scenarijų metodo sintezę, metodines nuostatos ir jų priimtinumo patikrinimo eksperimentu rezultatai.Reikšminiai žodžiai: verslas, strateginiai sprendimai, scenarijų metodas, daugiakriteris vertinimas, metodų sintezė.First Published Online: 21 Oct 2010